Sistem Manajemen Proyek Berbasis Website Dengan Metode Kanban - Florence Aurelia Widjaja; Bhustomy Hakim (Computer Science)
The advancement of digital technology has created a growing demand for systems that support work effectiveness, particularly in project management. The Digital Learning Division at PT. Kurnia Ciptamoda Gemilang faces challenges in monitoring projects in a structured and timely manner, necessitating a web-based project management system tailored to the company’s specific needs. This study aims to design a standalone web-based project management system that is not yet integrated with existing systems but is structured to allow future integration. The system was developed using the Next.js framework, applying the Kanban method and the SDLC Waterfall development model. The research involved problem identification, literature review, and interviews with project managers to gather both functional and non-functional requirements. The results show that the developed system includes key features such as workspace management, member management, project and task management, task prioritization, deadline setting, and visualizations in the form of Kanban boards and calendars. Work efficiency is measured through the availability of a more structured workflow and a reduction in miscommunication during task assignment. The system was evaluated using the Black Box Testing method, and the results confirm that all features function according to specifications and meet the users' actual needs in the work environment. The system has proven effective in improving work efficiency, facilitating team coordination, and ensuring that projects proceed as planned.